2020
DOI: 10.25259/sni_789_2020
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured hidden intracranial aneurysm during mechanical thrombectomy: A case report

Abstract: Background: Acute ischemic stroke (AIS) patients have a higher prevalence of cerebral aneurysm than a healthy reference population. However, it was recently reported that cases of an unknown hidden aneurysm in AIS patients with large-vessel occlusion are rare. We report a rare case of subarachnoid hemorrhage (SAH) during mechanical thrombectomy (MT) using a stent retriever for AIS. Case Description: A 46-year-old patient with the right internal carotid artery terminal occlusion presented with the left-side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…When patients use vital signs, healthy big data can obtain real human hemodynamic parameters, such as velocity, differential pressure, wall intercept stress, and particle motion. It is of great significance for cardiovascular system optimization, preoperative prediction, and clinical intervention evaluation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When patients use vital signs, healthy big data can obtain real human hemodynamic parameters, such as velocity, differential pressure, wall intercept stress, and particle motion. It is of great significance for cardiovascular system optimization, preoperative prediction, and clinical intervention evaluation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 A few studies have also reported critical complications associated with rupture of hidden aneurysms due to mechanical stimulation of the stent retriever or thrombolysis. 4 , 5 Hidden cerebral aneurysms are frequently bifurcating (e.g., of the MCA and basilar artery tip), which is likely because blood flow is directed toward the aneurysms. 4 As such, sidewall-type hidden aneurysms are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Ruptured hidden aneurysms can be treated by endovascular techniques immediately [130,131], but unruptured ones later, after the patient suffered from acute symptomatic thrombosis, with adequate antiplatelet pretreatment [132].…”
Section: Potential Hemorrhagic Procedural Complicationsmentioning
confidence: 99%